Urban elementary school principals men and women - Guanzon, Lilia S. 1922- (s.n.], 1969)
The purpose of the study is to investigate the backgrounds and occupational careers of urban men and women principals and to gain insight into the emphasis that they assign to their professional activities in relation to the performance of their administrative and supervisory tasks. Using the demographic approach, the study provides a profile of a sector of the personnel in education in an urban setting, and contributes to a great extent to a better understanding of the principals as central figures in their schools.